Understanding experiences of neglected tropical diseases of the skin: a mixed-methods study to inform intervention development in Ethiopia - Michael Marks; David Mabey; Ruth Canter; Elizabeth Allen; Charles Opondo; Jennifer Palmer; Iris Mosweu; Jacob Novignon; Sinéad Langan; Maria Zuurmond; Catherine Pitt; Stephen L Walker; et al. (BMJ Global Health)
Background The WHO and Ethiopia’s Ministry of Health have developed strategies to expand and integrate services for co-endemic neglected tropical diseases (NTDs) which manifest in the skin. To inform these strategies, we aimed to understand the social, economic and health system context of skin NTD care in Kalu woreda, Amhara region, Ethiopia, where cutaneous leishmaniasis (CL) and leprosy are endemic.Methods Between October 2020 and May 2022, we surveyed and reviewed records of 41 primary healthcare facilities and explored common disease experiences in focus group discussions (n=40) and interviews with people affected by leprosy (n=37) and CL (n=33), health workers (n=23), kebele authorities and opinion leaders (n=33) and traditional healers (n=7). Opportunities for integrated skin NTD service provision were explored through policy document review, interviews with health officials (n=25), and stakeholder meetings.Results Availability of diagnostic supplies and health worker competence to provide skin care was very limited across primary healthcare facilities, particularly for CL. People with leprosy commonly sought care from healthcare facilities, while people with CL administered self-care or sought help from traditional healers. Travel and costs of care at specialised facilities outside the district inhibited timely care-seeking for both diseases. Transmission discourses shaped different understandings of who was affected by leprosy and CL and expectations of behaviour during and after treatment. Many policy actors felt that existing supply chain interventions, decentralised treatment approaches and community engagement initiatives for leprosy could also benefit CL, but others also warned against increasing care-seeking unless CL treatment could be provided on a scale commensurate with the large burden they perceived.Conclusion Our findings demonstrate significant gaps in the provision of care for skin NTDs within primary healthcare, very different health-seeking patterns for leprosy and CL, and a need to develop new models of care, especially for CL.